The transformation of public universities in Vietnam and their role in national innovation systems - Luan, Pham Dang Manh Hong (2025)
The concept of national innovation systems (NIS) has been commonly applied as a theoretical lens for researching innovation systems worldwide. This phenomenon has occurred also in Asia. Although underreported, the case of Vietnam is worth exploring, including the role of public universities (PUs) in the NIS and the transformation of these institutions in order to enhance their influence in this system. This qualitative study includes a literature review and in-depth interviews with eleven high-ranking managers from nine Vietnamese PUs to assess the transition of these universities toward innovation and entrepreneurship and their significant role in NIS, particularly for three characteristics identified in the gray literature: effective leadership, interdisciplinarity, and entrepreneurship. Insights from interviews revealed PUs’ strong leadership in NIS and the universities’ clear objectives and significant efforts to change toward innovation and entrepreneurship. However, institutional barriers rooted in the long-standing Soviet Union-style educational system, such as rigidly defined education boundaries and premature networking with industry, pose major constraints to change. The study offers suggestions to improve the Vietnamese PUs’ ability to promote innovation and entrepreneurship, including integrating interdisciplinary courses into the curriculum, establishing interdisciplinary offices, encouraging talent mobility between universities and industry as well as devising robust intellectual property rights.